Social support and life satisfaction among Hong Kong Chinese older adults: family first? - Yeung, Gladys T. Y. (Eur J Ageing, 2007)
Family members and friends are important for the psychological well being of older adults. The present study examined the relative contribution of these two sources of support to life satisfaction among Chinese older adults living in Hong Kong. The moderating role of familism, which represents the commitment of family members to the family, was also examined. One hundred and eight Chinese older adults participated in the study. Findings suggest that, in general, family support contributes more to the life satisfaction of older adults than does friend support. While emotional support from family members is beneficial to life satisfaction of older adults regardless of individual differences in familism, instrumental support contributes more to life satisfaction for older adults with higher familism.